The Effect of Chewing Gum on the Recovery of Intestinal Peristalsis in Post Partum Sectio Caesarea Mothers - Ramasari, Eka Alfiana; Purwanti, Heni; Hadiningsih, Eka Frenty; Sumiati, Sumiati (Institute Of Computer Science (IOCS), 2024)
Post-cesarean section surgery can cause a decrease in bowel movements. Dr. Data Hospital. Abdul Rivai, in August 2023 there were 66 caesarean section deliveries (51.2%) with a permanent decrease in intestinal peristalsis, namely 6 cases. Chewing gum is a form of sham feeding to stimulate the intestinal recovery process after surgery. Preliminary study at RSUD dr. Abdul Rivai Berau, it is known that there are cases of post-caesarean section mothers who experienced decreased intestinal peristalsis or did not increase intestinal peristalsis. To determine the effect of chewing gum on the recovery of intestinal peristalsis in post partum caesarean section mothers. Pre-experimental research type and One Group Pre-Test – Post-Test Design. The population is all post partum caesarean section mothers in the Postpartum Room at RSUD dr. There were 66 Abdul Rivai in Berau Regency in August 2023, based on the Lameshow formula with a sample of 35 people studied in December 2023. Instruments included a stethoscope, Xylitol gum and observation sheets. The sampling technique uses consecutive sampling. Data analysis used the Wilcoxon test. Frequency score of intestinal peristalsis before chewing gum in post partum caesarean mothers with a median of 2 times per minute and after chewing gum the median was 4. Obtained p value = 0.000 < ? : 0.05, meaning there is an effect of chewing gum on restoration of intestinal peristalsis. Chewing gum can improve the recovery of intestinal peristalsis in post partum caesarean section mothers.